Pré-concentração em sistema em fluxo acoplado In-line à GFAAS para especiação de selênio em amostras de interesse farmacêutico - Paiva, Ana Lúcia Silva Figueiredo De (2009)
Selenium is one essential element for live organisms; nevertheless, there is one small range between its toxicity and essentiality, which depends on the selenium species. Thus, the development of sensitive technique is of utmost importance. In this work a home-made mini column filled with LC-SAX was coupled to GFAAS auto sampler using FIA system, which was used for in-line pre-concentration. Preconcentration, elution and cleaning of the minicolumn in the FIA system were synchronized with GFAAS heating program. To speciation of Se compounds, 6 mL of sample, with two Se species, were prepared at pH 2.0 and 8.8, the elution was performed using 20 uL of nitric acid directly in the graphite tube. The 23 factorial design to verify the significance of the variables was employed, and a Doehlert matrix and response surface for optimal values observation was used. The optimized values for pH, pre-concentration flow rate and eluent concentration were 8.8, 4.0 mL min-1 and 2.8 mol L-1, respectively. When pH was studied in the range of 2 to 8 was noted that in pH 2 only Se(VI) was pre-concentrated, on another hand, in pH above 6 both Se(IV) and Se(VI) can be determined. In order to determine each species a system with three equations was proposed and this system was based on the sum of absorbances obtained in two different pH. The first equation was obtained in pH = 2.0 with Se(VI) analytical curve; the second is for Se(VI) too but in pH = 8.8, and the third one was obtained with Se(IV) analytical curve in pH = 8.8. The system presented for Se(IV) and Se(VI) respectively, the following characteristics: enrichment factor of the 108 and 74, consume indices of the 5.6 x 10-2 and 8.1 x 10-2 mL, concentration efficiency of the 37.0 e 25.4 FE min-1. The limit of detection were 49 and 31 ng L-1 for Se(IV) and Se(VI), respectively. The method shown satisfactory results for precision with coefficient of variation up to 5.5% for Se(VI) when 2.0 ug L-1 was tested (n=6). The accuracy was checked with certified reference material, Dogfish, and with recovery tests. There is no significant difference between obtained and certified values with 95% confidence level (t-test), and the recovery values were in the range of 99 to 110%. The method was applied in water and pharmaceutical samples and the results were satisfactory.